Muslim Consumer Behavior Towards Purchasing Food and Beverage Produtcs Without a Halal Label - Irmadatus Sholekhah; Dibyo Waskito Guntoro; Dwi Herlindawati (Universitas Trunojoyo Madura, 2026)
The expansion of food and beverage products without halal labels in Indonesia poses challenges for the country's Muslim-majority population, as Islamic law requires the consumption of halal products. This qualitative study explores the purchasing decisions of Muslim consumers toward non-halal-labeled products. Using a descriptive qualitative approach, data were collected through in-depth interviews with 14 Muslim consumers in Jember Regency, East Java, selected through snowball sampling. The qualitative approach was employed to capture the contextual factors and subjective considerations underlying consumers' decisions. The findings reveal a gap between consumers' awareness of the importance of halal certification and their actual purchasing behavior. Despite recognizing the halal label as an important indicator of religious compliance, many respondents continue to purchase non-labeled products based on trust in the product's ingredients, brand reputation, manufacturer, and assumptions of inherent halalness. Purchasing decisions are also influenced by social recommendations, urgent situations, and sensory factors such as taste and product popularity. In the absence of halal certification, consumers frequently rely on alternative indicators, including the producer's Muslim identity, product origin, and word-of-mouth information, to assess halal status. These findings highlight the complexity of Muslim consumer behavior and provide insights for policymakers and businesses in strengthening halal assurance and consumer trust.